INFLUENCE MANAGER'S INVESTMENT ATTITUDE ON ORGANIZATION ENVIRONMENT AND PORTFOLIO PERFORMANCE REKSADANA SHARES (Study on Mutual Fund Management Company Reksadana Shares in Indonesia) - Teddy Oswari; Dionysia Kowanda (Universitas Gunadarma, 2009)
The purpose of this research is to measures the effect of investment manager attitude through operational employees to mutual funds work attitude portfolio, to analyse how big the organizational environment effect together with investment manager attitude, through operational employees to mutual funds work attitude portfolio and analyse the effect of organizational envirobment to investment manage attitude in mutual funds company. The observation conducted in 72 mutual funds company, the data collecting using questionnaire that filled by the investment manager and to the operational employee who help and run mutual fundscompany. By using Anova statistical analysis, determiner cohesion parameter and methods, i.e. Sharpe, Treynor and Jensen to know whether or not there’d be effect among operational employees, organisational environment, and work portfolio in matual funds company in Indonesia. In conclusion, the effect of organisational environment (X1) to operational employees (X2) has the big effect, the effect of organisational environment (X1)to investment manager attitude (X3) has the second biggest effect, and the third is the effect of the operational employees (X2) to work attitude using (Y Treynor), the fourth is the effect of operational employees (X2) to work attitude using (Y Jensen), and the smallest effect is the operational employee (X2) to work attitude using (Y Shape). From the analysis it is discovered an indication that mutual funds company put the employees more important than their orientation on gaining return.Keywords: sikap manajer investasi, karyawan pelaksana, lingkungan organisasi, reksadana saham1